Nanotechnology for microelectronics and optoelectronics - Martinez-Duart, J. M. (Elsevier, 2006)
When solids are reduced to the nanometer scale, they exhibit new and exciting behaviours which constitute the basis for a new generation of electronic devices. Nanotechnology for Microelectronics and Optoelectronics outlines in detail the fundamental solid-state physics concepts that explain the new properties of matter caused by this reduction of solids to the nanometer scale. Applications of these electronic properties is also explored, helping students and researchers to appreciate the current status and future potential of nanotechnology as applied to the electronics industry. * Explains the behavioural changes which occur in solids at the nanoscale, making them the basis of a new generation of electronic devices. * Laid out in text-reference style: a cohesive and specialised introduction to the fundamentals of nanoelectronics and nanophotonics for students and researchers alike.